The AU, NEPAD and the Promotion of Good Governance in Africa - John K. Akokpari (Nordic Journal of African Studies, 2004)
This article argues that good governance has been elusive in much of Africa. The failure of the Organisation for African Unity (OAU) to address Africa’s developmental challenges, including the crisis of governance, led to its demise. In an attempt to promote good governance, as well as to address Africa’s post-cold war legion of challenges, the successor organisation, the African Union (AU) and its attendant development programme, the New Partnership for African Development (NEPAD), were established. These projects embody an innovative peer review mechanism by which African governments are assessed in terms of their progress towards good governance. Countries passing the review test would be rewarded with western aid. NEPAD, the AU and the review mechanism have exited hope because of the expectation that these would reorder governance policies in Africa. However, the article contends that in spite of the expectations and euphoria generated by these projects, they have a truncated capacity to induce good governance. This is not only due to the intrinsic contradictions in these initiatives, but also because of a confluence of factors, including the vulnerability of the projects to manipulation by African leaders, the preponderance of neo-patrimonial politics in Africa, the confusing relations between especially NEPAD and the AU, and the tendency for the G8 – Africa’s key partners – to renegade from their initial aid commitments.